Exposure‐response analysis after subcutaneous administration of RBP‐7000, a once‐a‐month long‐acting Atrigel formulation of risperidone. (31st March 2017) - Ivaturi, Vijay; Gopalakrishnan, Mathangi; Gobburu, Jogarao V. S.; Zhang, Weiyan; Liu, Yongzhen; Heidbreder, Christian; Laffont, Celine M.
Abstract : Aims: A new, long‐acting, subcutaneous (SC) formulation of risperidone (RBP‐7000) has been developed for the treatment of schizophrenia to address issues of non‐adherence associated with oral risperidone treatment. The objective of this work was to establish an exposure‐response relationship between total active moiety (AM) plasma exposure (risperidone + 9‐hydroxy‐risperidone) and Positive and Negative Syndrome Scale (PANSS) or Clinical Global Impression severity (CGI‐S) scores using data from a registration trial. Methods: This was a Phase 3 randomized, double‐blind, placebo‐controlled, multicenter study in 354 patients to evaluate the efficacy, safety and tolerability of RBP‐7000 (90 mg and 120 mg). Non‐linear mixed effects modelling was used to develop an integrated population pharmacokinetic/pharmacodynamic (PK/PD) model that included a joint PK model for risperidone and 9‐hydroxy‐risperidone with placebo and drug‐effect models to establish the relation between total AM exposure and PANSS or CGI‐S scores. Results: CYP2D6 poor and intermediate metabolizers had lower formation rates of 9‐hydroxy‐risperidone (94% and 76% lower, respectively) compared to the extensive CYP2D6 metabolizers. The maximum placebo‐corrected relative decrease in PANSS score from baseline following RBP‐7000 treatment was 5.4%, half of which could be achieved at plasma concentrations of 4.6 ng ml −1 of the total AM. A proportional odds model for the CGI‐S score related the total AM plasma concentration to the probability of improving/worsening scores over time. Conclusions: Exposure‐response analysis was established between total AM concentrations and PANSS and CGI‐S scores, with good precision in parameter estimates. CYP2D6 phenotype on risperidone metabolism was the only identified covariate.